Detection and Characterization of Enteropathogenic and Shiga Toxin-Producing Escherichia coli Strains in Rattus spp. from Buenos Aires - Blanco Crivelli, Ximena; Bonino, María P.; Von Wernich Castillo, Paula; Navarro, Armando; Degregorio, Osvaldo; Bentancor, Adriana (Frontiers in Microbiology, 2018)
Enteropathogenic Escherichia coli (EPEC) and Shiga toxin-producing E. coli (STEC) are pathovars of E. coli that impact human health by causing childhood diseases. In this work, 118 synanthropic rodents of the genus Rattus from Buenos Aires, Argentina were evaluated as EPEC and STEC carriers. Rectal swab samples from captured animals were evaluated by conventional PCR to detect the presence of the eae, stx1, stx2, and rfbO157 genes. Twenty-one isolates were obtained (17 EPEC isolates from seven animals and four STEC isolates from the same animal). All EPEC isolates tested negative for the presence of the bfpA gene. One EPEC isolate carried the iha gene, and five EPEC isolates carried the toxB gene. STEC isolates exhibited two different virulence profiles: stx1a/stx2a/stx2c/stx2d/saa/ehxA/subA (3/4) and stx1a/stx2a/saa/ehxA/subA (1/4). EPEC isolate serotypes included O109:H46 (7), O71:H40 (4), O71:NM (2), O138:H40 (1), O108:H21 (1), O88:H25 (1), and O76:NM (1), and STEC isolates belonged to the O108:H11 (4) serotype. Antimicrobial susceptibility testing was carried out, and resistance to tetracycline was observed in one EPEC strain. Our results demonstrate that Rattus spp. may act as carriers of EPEC and STEC strains and may be involved in the epidemiology of diarrheal disease in infancy.